2017
DOI: 10.1038/s41598-017-10738-8
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a new member of Iridoviridae, Shrimp hemocyte iridescent virus (SHIV), found in white leg shrimp (Litopenaeus vannamei)

Abstract: A newly discovered iridescent virus that causes severe disease and high mortality in farmed Litopenaeus vannamei in Zhejiang, China, has been verified and temporarily specified as shrimp hemocyte iridescent virus (SHIV). Histopathological examination revealed basophilic inclusions and pyknosis in hematopoietic tissue and hemocytes in gills, hepatopancreas, periopods and muscle. Using viral metagenomics sequencing, we obtained partial sequences annotated as potential iridoviridae. Phylogenetic analyses using am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
143
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(166 citation statements)
references
References 15 publications
15
143
0
8
Order By: Relevance
“…Shrimps ( L. vannamei , average weight 8 g each) were purchased from the local shrimp farm in Zhuhai, Guangdong Province, China, and fed with a commercial diet in a recirculating water tank system filled with air-pumped sea water (2.5% salinity) at 28 °C. Before all experiment treatments, the shrimps (5% of total) were detected and confirmed to be free of common pathogens including white spot syndrome virus (WSSV), yellow head virus (YHV), taura syndrome virus (TSV), shrimp hemocyte iridescent virus (SHIV, also known as CQIV), infectious hypodemal and hematopoietic necrosis virus (IHHNV) and Vibrio parahaemolyticus by PCR or RT-PCR methods according to standard operation procedures by Panichareon et al (71) and Qiu et al (72). Because many genes from the shrimp canonical Toll-Dorsal pathway can be activated by Gram-negative (G - ) bacteria (42, 46), V. parahaemolyticus thus was used here as a positive activator of the shrimp Toll-Dorsal pathway.…”
Section: Methodsmentioning
confidence: 99%
“…Shrimps ( L. vannamei , average weight 8 g each) were purchased from the local shrimp farm in Zhuhai, Guangdong Province, China, and fed with a commercial diet in a recirculating water tank system filled with air-pumped sea water (2.5% salinity) at 28 °C. Before all experiment treatments, the shrimps (5% of total) were detected and confirmed to be free of common pathogens including white spot syndrome virus (WSSV), yellow head virus (YHV), taura syndrome virus (TSV), shrimp hemocyte iridescent virus (SHIV, also known as CQIV), infectious hypodemal and hematopoietic necrosis virus (IHHNV) and Vibrio parahaemolyticus by PCR or RT-PCR methods according to standard operation procedures by Panichareon et al (71) and Qiu et al (72). Because many genes from the shrimp canonical Toll-Dorsal pathway can be activated by Gram-negative (G - ) bacteria (42, 46), V. parahaemolyticus thus was used here as a positive activator of the shrimp Toll-Dorsal pathway.…”
Section: Methodsmentioning
confidence: 99%
“…Partial sequences were obtained by viral metagenomics, and phylogenetic calculations based on the sequences of major capsid protein and ATPase showed that SHIV is a new iridescent virus, which could not be clustered into any of the five known genera of Iridoviridae. Based on the sequences a diagnostic PCR was developed for detecting this novel virus threatening shrimp farming industry in China (Qiu et al, 2017).…”
Section: Discovery Of Novel Virusesmentioning
confidence: 99%
“…Globally, viral diseases have been acknowledged as a huge threat to shrimp aquaculture industry. Among the viruses reported for crustacean, Shrimp hemocyte iridescent virus (SHIV) was a newly found virus isolated from diseased white leg shrimp Penaeus vannamei in December of 2014 in Zhejiang Province of China, which can cause massive mortality to P. vannamei [1], the most important crustacean for global aquaculture. The virus has a typical icosahedral structure with a mean diameter around 150 nm [1].…”
Section: Introductionmentioning
confidence: 99%
“…Among the viruses reported for crustacean, Shrimp hemocyte iridescent virus (SHIV) was a newly found virus isolated from diseased white leg shrimp Penaeus vannamei in December of 2014 in Zhejiang Province of China, which can cause massive mortality to P. vannamei [1], the most important crustacean for global aquaculture. The virus has a typical icosahedral structure with a mean diameter around 150 nm [1]. Evidences from histopathological study, transmission electron microscope (TEM) of ultrathin sections, and in situ hybridization (ISH) indicated that SHIV may mainly infect the hematopoietic tissue and hemocytes in P. vannamei [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation